ANALISIS PENGARUH AKTIVA PRODUKTIF TERHADAP LABA PADA BANK UMUM DEVISA - Ifanka, Tia; Hariyani, Happy Febrina (Journal of Financial Economics & Investment, 2023)
This study aims to determine the effect of Earning Assets: Disbursed Loans, Investments in Securities, Placements in Other Banks on Profits at Foreign Exchange Commercial Banks registered with Bank Indonesia (BI) in 2015-2019. The population in this study is the National Private Foreign Exchange Commercial Banks registered with BI during the observation period from 2015 to 2019 which amounted to 41 banking companies. As for the determination of the sample in this study using the census method where all the population was determined as a sample which amounted to 41 National Private Commercial Banks of foreign exchange. The analysis technique uses panel data regression analysis (pooled data). The results of this study are, simultaneously there is a positive and significant influence between loans disbursed, investment in securities and placements in other banks on profits at foreign exchange commercial banks. Meanwhile, partially, those that have a positive and significant influence on Profit are Disbursed Credit and Securities Investment, while those that have a negative and significant influence on Profit are Placements with Other Banks.